2022
DOI: 10.1002/cam4.5158
|View full text |Cite
|
Sign up to set email alerts
|

BCR::ABL1 levels at first month after TKI discontinuation predict subsequent maintenance of treatment‐free remission: A study from the “GRUPPO TRIVENETO LMC”

Abstract: We analyzed BCR::ABL1 expression at stop and in the first month after discontinuation in 168 chronic myeloid leukemia patients who stopped imatinib or 2nd generation tyrosine kinase inhibitors (2G‐TKIs) while in sustained deep molecular response. Patients were divided among those who maintained response (group 1, n = 123) and those who lost major molecular response (group 2, n = 45). Mean BCR::ABL1 RNA levels 1 month after discontinuation were higher in group 2 tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The median time from TKI discontinuation and the loss of MMR to TKI treatment restarting in the TFR failure group was 4 months and 4.4 months, respectively. This report suggests a threshold value of BCR::ABL1 RNA expression for TKI discontinuation, where an absolute value of <0.0051% at six months was associated with an extremely high chance (over 90%) of maintaining MMR after treatment discontinuation, both for patients stopping imatinib or 2G-TKI [ 60 ]. This result corroborates a Canadian report showing that a shorter BCR::ABL1 doubling time was associated with a higher rate of TFR failure [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The median time from TKI discontinuation and the loss of MMR to TKI treatment restarting in the TFR failure group was 4 months and 4.4 months, respectively. This report suggests a threshold value of BCR::ABL1 RNA expression for TKI discontinuation, where an absolute value of <0.0051% at six months was associated with an extremely high chance (over 90%) of maintaining MMR after treatment discontinuation, both for patients stopping imatinib or 2G-TKI [ 60 ]. This result corroborates a Canadian report showing that a shorter BCR::ABL1 doubling time was associated with a higher rate of TFR failure [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that all CP CML patients may have access to a successful TFR even when non-optimal features are present, provided that there is an optimal duration of DMR before TKI stop and that close molecular monitoring is guaranteed, especially during the first months of TFR [ 3 ]. Our group recently showed that BCR::ABL1 value at 1 month after stop is strongly predictive of subsequent maintenance of TFR, and this value may be used to safely model the frequency of monitoring during TKI discontinuation [ 16 ].…”
mentioning
confidence: 99%
“…The difference with our analysis reflects the multicentric nature of this study, with patients followed in seven different units with molecular results not centralized but detected in different molecular laboratories with different sensitivity. 8 Although "early" recurrence is the most frequent, a longer follow-up and an increased number of TFR-attempting patients might help to detect a threshold at a subsequent monitoring timepoint in order to predict "late" recurrence. In the future, digital droplet PCR approach could replace the conventional monitoring strategy for TFR setting as recently proved by different groups.…”
mentioning
confidence: 99%